Maintenance architecture - Sample, Hilary (The MIT Press, 2016)
An inventive examination of a crucial but neglected aspect of architecture, by an architect writing to architects
Includes index. - Includes bibliographical references and index
Keywords: Instandhaltung; Akzeptanz; Architektur; Bauunterhaltung; Post Occupancy Evaluation; Benutzung; Architecture / Human factors; Buildings / Maintenance / Miscellanea